2016
DOI: 10.1016/j.meatsci.2015.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Excess glycogen does not resolve high ultimate pH of oxidative muscle

Abstract: Skeletal muscle glycogen content can impact the extent of postmortem pH decline. Compared to glycolytic muscles, oxidative muscles contain lower glycogen levels antemortem which may contribute to the higher ultimate pH. In an effort to explore further the participation of glycogen in postmortem metabolism, we postulated that increasing the availability of glycogen would drive additional pH decline in oxidative muscles to equivalent pH values similar to the ultimate pH of glycolytic muscles. Glycolysis and pH d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 45 publications
3
57
3
4
Order By: Relevance
“…Ryu and Kim (2005) reported that increased percentage of white (Type IIb) muscle fibers in pork longissimus muscle was associated with increased glycolytic rate, and increased L* values at 45 min and 24 h postmortem, and decreased a* values at 45 min postmortem. England et al (2016) reported greater myoglobin concentration in pork masseter muscle [predominately composed of slow (red) muscle fibers] than longissimus muscle, which has a greater proportion of fast (white) muscle fibers. Cross et al (2018) identified QTL for myoglobin concentration of pork longissimus on chromosome 14 that were associated with calcineurin regulation.…”
Section: Resultsmentioning
confidence: 96%
“…Ryu and Kim (2005) reported that increased percentage of white (Type IIb) muscle fibers in pork longissimus muscle was associated with increased glycolytic rate, and increased L* values at 45 min and 24 h postmortem, and decreased a* values at 45 min postmortem. England et al (2016) reported greater myoglobin concentration in pork masseter muscle [predominately composed of slow (red) muscle fibers] than longissimus muscle, which has a greater proportion of fast (white) muscle fibers. Cross et al (2018) identified QTL for myoglobin concentration of pork longissimus on chromosome 14 that were associated with calcineurin regulation.…”
Section: Resultsmentioning
confidence: 96%
“…Once formed, AMP is converted to IMP by AMP deaminase, which leads eventually to the depletion of the adenine nucleotide pool (Greaser, 1986). The loss of adenine nucleotides has previously been shown to mediate premature ter-385 mination of postmortem metabolism (England et al, 2016). Yet, adenine nucleotides were not depleted by 120 min, suggesting that adenine nucleotides were not limiting, at least during the first 120 min postmortem.…”
Section: Glycolytic Metabolites and Adenine Nucleotidesmentioning
confidence: 99%
“…We previously showed that PFK starts to lose activity near pH 5.9 and becomes completely inactive at pH 5.5, which halts glycolytic flux and pH decline (England et al, 2014). In some cases, however, the depletion of adenine nucleotides (ATP, ADP, and 45 AMP) arrest glycolysis while PFK presumably is still functioning (England et al, 2016). Thus, any one or a combination of the aforementioned mechanisms can lead to the cessation of postmortem metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The later changes and indicators of meat quality depend on the level of glycogen and the speed of its decomposition in the process of the so-called anaerobic glycolysis (2,22). Glycogen content significantly determines the final pH of meat (5,6) and has a bearing on plenty of its indicators, such as hydration properties, shear force, colour, and cooling loss (4,11,23).…”
Section: Introductionmentioning
confidence: 99%